2014
DOI: 10.1603/ec13521
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Trends in Mixed <I>Bemisia tabaci</I> (Hemiptera: Aleyrodidae) Cryptic Species Populations in Commercial Poinsettia Under Biological Control- and Insecticide-Based Management

Abstract: Bemisia tabaci (Gennadius) is an economically important pest of agricultural and ornamental plants worldwide and is now widely recognized as a cryptic species complex. In North America, B. tabaci is a particularly important pest of greenhouse poinsettia. In poinsettia production, two cryptic species from the B. tabaci complex, Mediterranean and Middle East Minor 1, often infest crops simultaneously. Differences in pesticide susceptibility between these two cryptic species have the potential to influence grower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Cryptic species have important implications for taxonomic, evolutionary, and biodiversity studies, but their presence in pest taxa also has economic and regulatory implications (Piffaretti et al 2013;Rebijith et al 2014). Several studies have considered the impact of cryptic species on pest management (Frewin et al 2014;Ovalle et al 2014), biological control strategies (Derocles et al 2015), the detection of invasive species (Blacket et al 2015;Li et al 2015), and quarantine inspections (Kang et al 2015). The most obvious implications of DNA barcoding relate to its capacity to discriminate the members of cryptic species complexes (Robe et al 2013).…”
Section: Cryptic Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cryptic species have important implications for taxonomic, evolutionary, and biodiversity studies, but their presence in pest taxa also has economic and regulatory implications (Piffaretti et al 2013;Rebijith et al 2014). Several studies have considered the impact of cryptic species on pest management (Frewin et al 2014;Ovalle et al 2014), biological control strategies (Derocles et al 2015), the detection of invasive species (Blacket et al 2015;Li et al 2015), and quarantine inspections (Kang et al 2015). The most obvious implications of DNA barcoding relate to its capacity to discriminate the members of cryptic species complexes (Robe et al 2013).…”
Section: Cryptic Speciesmentioning
confidence: 99%
“…Since DNA barcoding reliably identifies both immatures and adults (Shin et al 2013), and can differentiate introduced and native pests (Chown et al 2008), it has been used to help manage species complexes in agricultural systems (Li et al 2011;Frewin et al 2014). Such applications are important because insecticide resistance can vary between closely related species, and even between genotypes of the same species (van Toor et al 2008).…”
Section: Practical Implications Of Dna Barcodingmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prevalent species in North America (formerly considered biotypes) are characterized by a high invasive ability (Middle East-Asia Minor 1 (MEAM1) or B biotype) and an innate ability to rapidly develop a high-level of insecticide resistance that persists in the absence of exposure (Mediterranean or Q biotype) [3,4]. Resistance to conventional pesticides including newer chemistries is observed [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from the UK, where B. tabaci is subject to eradication, demonstrated that it has been intercepted annually in the UK on imported plant material since 1987, in particular on poinsettias [8]. In Ontario (Canada), where B. tabaci is not known to overwinter outdoors, surveys of commercial greenhouse operations routinely find this whitefly in young poinsettia plants [4]. Starting a crop with high pest infestations makes it very difficult for growers to successfully use biological controls, which are best used in a preventative rather than a curative manner.…”
Section: Introductionmentioning
confidence: 99%